Description of Treatment Compliance of Patients with Pulmonary Tuberculosis at the Pulmonary Polyclinic of Tarakan Regional Hospital, Central Jakarta - Alviana, Tresya; Mamudi, Chrispian Oktafbipian; Wician, Fendra (Jurnal MedScientiae, 2026)
Pulmonary tuberculosis (TB) remains a major health challenge in Indonesia, particularly in urban areas such as Central Jakarta. This study aims to describe medication adherence among pulmonary TB patients at the Pulmonary Clinic of Tarakan Regional General Hospital, Central Jakarta, during January–December 2023. The study design was descriptive with a cross-sectional approach. The study sample consisted of 122 outpatients who met the inclusion criteria. Data were collected using the Probabilistic Medication Adherence Scale (ProMAS) questionnaire and medical records, then analyzed univariately using SPSS. The results showed that the majority of respondents were male (57.38%), adults (73.77%), and most had a Medication Swallowing Supervisor (82.61%). The level of medication adherence was low, with 53.32% of patients having low adherence, 46.72% having moderate adherence, and none achieving high adherence. Factors influencing adherence included knowledge of treatment for at least 6 months (84.4%), high motivation to recover and self-confidence (≥96.7%), very strong family support (>95%), good distance access to health facilities for some respondents, and the educational and supportive role of health workers/PMOs. These findings indicate that health education interventions, strengthening the role of families, increasing patient motivation, and optimizing PMO supervision are still needed to achieve optimal adherence levels, so that the success of TB therapy and elimination can be maximized.